PENGEMBANGAN KAWASAN BUFFER ZONE TANJUNG LESUNG SEBELUM TERJADI TSUNAMI PADA KECAMATAN PANIMBANG DAN CIGEULIS - Rohani, Elisa Dwi; Ramadhan, Bagus (Universitas Merdeka Malang, 2019)
Tanjung Lesung is located in Pandeglang district, Banten Province, West Java, is a prospective area for tourism activities. Based on PP No. 50 of 2011 and PP No. 26 of 2012 the Tanjung Lesung region was included in the KSPN and became a National Tourism Special Economic Zone . This study aims to provide direction for strategic tourism development and management in the post-tsunami Tanjung Lesung buffer zone so that the focus of development is not only on the core area but also on buffer zones to improve people's quality of life and encourage tourism as an alternative in improving the welfare of surrounding communities Tanjung Lesung area, and restore the image of tourism after the tsunami. This research uses qualitative methods by multiplying and relying on empirical data in depth through a series of techniques with the required data collection techniques including observation, interviews, and focus group discussions. The condition of the core area of Tanjung Lesung after the Tsunami has many things that need to be corrected, so the hope that intervention from government activities in tourism recovery and development will not only focus on the core zone but also on the buffer zone of Sawer Curug, Cipanon Village and Liwungan Island. In addition, a development strategy that can be carried out to raise and introduce these three attractions is by creating a special adventure tour package because the existing conditions still lack infrastructure, so the first strategy is market penetration is a tourism development strategy that will be carried out.